E-module for geometric transformation visualization: A case study on generation Z mathematics education - Pratama, David; Darojat, Latifah (Universitas Islam Negeri Raden Intan Lampung, 2025)
Teaching transformation geometry in schools requires visualization tools to enhance students' conceptual understanding. Therefore, mathematics education students need to be equipped with adequate visualization skills. This study aimed to develop an interactive e-module based on YouTube video tutorials and simple projects to help students, particularly Generation Z, visualize transformation geometry concepts. The development model employed was the ADDIE (Analysis, Design, Development, Implementation, Evaluation). The findings indicated that the developed interactive e-module was valid (88.2%, excellent category), practical (75%, good category), and effective (94.3%) in supporting students in visualizing transformation geometry concepts. Integrating YouTube tutorial videos and simple projects facilitates students in learning and understanding the visualization of transformation geometry effectively and comprehensively. This study has implications for integrating technology-based interactive tools in learning, which can significantly enhance student engagement and mastery of abstract mathematical concepts.